SASI – SUS : a política de saúde para os povos indígenas na Casai Cuiabá - Oliveira, Karolline Rodrigues de (2019)
This research aim was to analyze the indigenous health policy at the secondary and tertiary level of care at the Casa de Saúde Indígena (CASAI) Cuiabá, by identifying the profile of the users of this Subsystem of Attention to Indigenous Health (SASI-SUS), the establishments and the health services most accessed by them in medium and high complexity units in the city of Cuiabá and Várzea Grande. The empirical field of research is the Cuiabá Indigenous Health House, a unit that makes up the Special Indigenous Sanitary District (DSEI) Cuiabá in the SASI-SUS. Thus, although currently the DSEI Cuiabá counts on two other CASAIs, one in Tangará da Serra and another in Rondonópolis, just the CASAI Cuiabá composed the study. This research was documentary and bibliographical, with quantitative nature. In order to reach established proposals and deepen the knowledge about health policy for indigenous peoples, a historical context of the process of struggle for social rights was carried out, which resulted in the current configuration of a Health Subsystem for these peoples. Thus, we approached the historicity of the struggle of these traditional peoples for social rights from the 1980s, identifying it in the midst of the constitution of a differentiated health policy to meet the specificities inherent in the life context of indigenous peoples. It is understood that SASI-SUS was the result of the Brazilian indigenous movement and its articulations and pressures under the State. We conclude that, despite its limitations and difficulties in its implementation, this Subsystem was constituted and still constitutes a differentiated service network within the Unified Health System and is essential in guaranteeing access to health by indigenous peoples, not only in the primary level, as well as at the secondary and tertiary levels. CASAI Cuiabá assumes the aspect of a regional unit of SASI-SUS, since it is located in a regional health center that concentrates most of the services of medium and high complexity, which implies serving a considerable number of users of different ethnicities derived not only from the DSEI Cuiabá but also from other DSEIs.